Lidocaine pre-treatment for Succinylcholine induced postoperative myalgia and associated factors: Longitudinal study - Fassil Mihretu; Telake Azale; Foziya Mohammed; Amare Agumas; Sara Timerga; Aynalem Befikadu (Surgery Open Science)
Introduction: Postoperative myalgia in surgical patients is mainly caused by the routinely administered depolarizing muscle relaxant, Succinylcholine. There are many proposed strategies but no one were indicated as ideal preventive mechanisms for Succinylcholine induced post-operative myalgia. Even if data were sparse, Lidocaine pretreatment can reduce postoperative myalgia which requires further supportive evidences urging the initiation of this study. Methods: Prospective longitudinal cohort study was conducted from March to May 2021 at Dessie Comprehensive Specialized Hospital on 208 adult surgical patients. Patients pretreated with Lidocaine preoperatively were grouped as exposed and others as unexposed. Patients meeting the inclusion criteria during the study period were selected sequentially from the daily operation schedule list. Postoperative myalgia level was measured using post-operative myalgia survey repeatedly. The result was analyzed by Cochran's Q test and generalized estimating equation (GEE). Adjusted odds ratio with 95 % confidence interval and p value < 0.05 was used to show the difference, direction and strength of association. Result: Exposure specific incidence rate showed that 22 %, 22 % and 29.8 % of patients exposed to Lidocaine and 40.6 %, 42.7 % and 34 % not exposed to Lidocaine developed myalgia at 12, 24, and 48 h respectively. There is no significant difference in the incidence of myalgia over time between the repeated measurements in Lidocaine exposed patients (p = 0.513) but in non-exposed patients (p = 0.003). Also, there is no difference in the distribution of other predictors between Lidocaine exposed and non-exposed groups (p > 0.05). Exposure to Lidocaine reduces postoperative myalgia significantly [AOR = 0.33, 95 % CI = (0.17,0.66)]. Multimodal analgesia [AOR = 0.32, 95 % CI = (0.18,0.55)], non-steroidal anti-inflammatory drugs alone [AOR = 0.47, 95 % CI = (0.29,0.76)], postoperative immobility [AOR = 0.61, 95 % CI = (0.47,0.8)], and being male [AOR = 0.48, 95 % CI = (0.26,0.87)] were other determinants in reducing Succinylcholine induced postoperative myalgia. Conclusion: Lidocaine pretreatment can significantly reduce the occurrence of Succinylcholine induced postoperative myalgia. Additionally, usage of multimodal analgesia with non-steroidal anti-inflammatory drugs or even only non-steroidal anti-inflammatory drugs in the intraoperative and postoperative period can reduce Succinylcholine induced postoperative myalgia.